New Enhanced Authentication Protocol for Internet of Things - Mourade Azrour; Jamal Mabrouki; Azedine Guezzaz; Yousef Farhaoui (Big Data Mining and Analytics)
Internet of Things (IoT) refers to a new extended network that enables to any object to be linked to the Internet in order to exchange data and to be controlled remotely. Nowadays, due to its multiple advantages, the IoT is useful in many areas like environment, water monitoring, industry, public security, medicine, and so on. For covering all spaces and operating correctly, the IoT benefits from advantages of other recent technologies, like radio frequency identification, wireless sensor networks, big data, and mobile network. However, despite of the integration of various things in one network and the exchange of data among heterogeneous sources, the security of user’s data is a central question. For this reason, the authentication of interconnected objects is received as an interested importance. In 2012, Ye et al. suggested a new authentication and key exchanging protocol for Internet of things devices. However, we have proved that their protocol cannot resist to various attacks. In this paper, we propose an enhanced authentication protocol for IoT. Furthermore, we present the comparative results between our proposed scheme and other related ones.